A High-avidity WT1-reactive T-Cell Receptor Mediates Recognition of Peptide and Processed Antigen but not Naturally Occurring WT1-positive Tumor Cells. Issue 3 (April 2016) - Jaigirdar, Adnan; Rosenberg, Steven A.; Parkhurst, Maria
Abstract : Wilms tumor gene 1 ( WT1 ) is an attractive target antigen for cancer immunotherapy because it is overexpressed in many hematologic malignancies and solid tumors but has limited, low-level expression in normal adult tissues. Multiple HLA class I and class II restricted epitopes have been identified in WT1, and multiple investigators are pursuing the treatment of cancer patients with WT1 -based vaccines and adoptively transferred WT1 -reactive T cells. Here we isolated an HLA-A*0201-restricted WT1 -reactive T-cell receptor (TCR) by stimulating peripheral blood lymphocytes of healthy donors with the peptide WT1 :126-134 in vitro. This TCR mediated peptide recognition down to a concentration of ∼0.1 ng/mL when pulsed onto T2 cells as well as recognition of HLA-A*0201 + target cells transfected with full-length WT1 cDNA. However, it did not mediate consistent recognition of many HLA-A*0201 + tumor cell lines or freshly isolated leukemia cells that endogeneously expressed WT1 . We dissected this pattern of recognition further and observed that WT1 :126-134 was more efficiently processed by immunoproteasomes compared with standard proteasomes. However, pretreatment of WT1 + tumor cell lines with interferon gamma did not appreciably enhance recognition by our TCR. In addition, we highly overexpressed WT1 in several leukemia cell lines by electroporation with full-length WT1 cDNA. Some of these lines were still not recognized by our TCR suggesting possible antigen processing defects in some leukemias. These results suggest WT1 :126-134 may not be a suitable target for T-cell based tumor immunotherapies. Abstract : Supplemental Digital Content is available in the text.